2019
DOI: 10.3390/sym11091070
|View full text |Cite
|
Sign up to set email alerts
|

Oblique Stagnation Point Flow of Nanofluids over Stretching/Shrinking Sheet with Cattaneo–Christov Heat Flux Model: Existence of Dual Solution

Abstract: In the present work we consider a numerical solution for laminar, incompressible, and steady oblique stagnation point flow of Cu − water nanofluid over a stretching/shrinking sheet with mass suction S . We make use of the Cattaneo–Christov heat flux model to develop the equation of energy and investigate the qualities of surface heat transfer. The governing flow and energy equations are modified into the ordinary differential equations by similarity method for reasonable change. The subsequent ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(35 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…Anjum et al 24 modeled the flow of a second‐grade fluid with the Cattaneo–Christov model past a Riga‐plate. Li et al 25 analyzed the Cu–water nanofluid flow over a stretching or shrinking sheet with the Cattaneo–Christov model. Reddy et al 26 studied the heat transfer characteristics of Prandtl non‐Newtonian nanofluid flow induced by a moving sheet with the Cattaneo–Christov heat flux model with the state of zero mass flux at the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Anjum et al 24 modeled the flow of a second‐grade fluid with the Cattaneo–Christov model past a Riga‐plate. Li et al 25 analyzed the Cu–water nanofluid flow over a stretching or shrinking sheet with the Cattaneo–Christov model. Reddy et al 26 studied the heat transfer characteristics of Prandtl non‐Newtonian nanofluid flow induced by a moving sheet with the Cattaneo–Christov heat flux model with the state of zero mass flux at the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Hayat et al 47 studied the flow of a Jeffrey fluid toward a stagnation point on a stretchable surface in a double stratification medium with the C–C model. Li et al 48 gave the dual solutions for suction effects on the flow of a copper–water nanofluid near stagnation point over a stretching/shrinking sheet with the C–C model. Hayat et al 49 addressed the flow of a second‐grade fluid sandwiched between two parallel plates in the presence of heat generation/absorption and the C–C model.…”
Section: Introductionmentioning
confidence: 99%
“…Raju et al [32] investigated nanofluid over non-linear stretching surface and found dual solutions. Oblique stagnation point flow of nanofluid on shrinking surface was examined by Li et al [33] and successfully noticed dual solutions in the range of stretching/shrinking parameter. Nanofluid with the effect of Soret and Dufour was investigated and noticed a dual solution without performing the analysis of the stability of the solutions [34].…”
Section: Introductionmentioning
confidence: 99%